“A wise criminal policy”. The ‘boys and girls of Salò’ in the jurisprudence of the Italian court of cassation (Italian Review of Legal History, 2019)
Even thought, over the last decades, many studies have been devoted to the issue of the Social Italian Republic, various aspects concerning the consent to republican Fascism are still awaiting full investigation, in particular as far as regards young people.As a matter of fact, after the armistice with the Allied was announced on September 8th 1943, thousands of young boys joined the army of the Republic of Salò, thus continuing the alliance with the Germans. Also many young girls actively collaborated with the occupying German armed forces and the German puppet Republic of Salò.After the Liberation Day, many young people that had fought at the side of Republic of Salò and against the Resistance were charged with collaboration with the Germans.The decree n. 159 of 27th July 1944, which consolidated the former enactments on the subject into one law, punished collaborators according to the Military Penal Code of 1941 (even if not members of the armed forces), which in these cases called for the death penalty or lengthy prison sentences.The decree n. 142 of 22nd April 1945, which specifically addressed the crimes of collaboration committed during the German military occupation of Northern Italy, established special court of assize. Though in theory they were expected to have fully performed their duties within six months, in practice they continued to sentence for two years as a special section of ordinary assize courts.Their sentences could be appealed in the special section of the Court of Cassation established in Milan, and subsequently in the Court of Cassation in Rome after the Court in Milan was abolished.The special courts of assize were composed of a professional judge as a president and four jurors selected by the National Liberation Committee, which, in addition, could choose prosecutors from a pool of anti-Fascist lawyers.It is important to keep in mind that on the one hand, transitional legislators were not confident in the ordinary judiciary, which was still considered linked to Fascism, and that on the other hand, special court of assize guaranteed popular participation in the administration of justice.When it became apparent that the goal of achieving democracy was emerging in Italy’s post-war society, it was up to the judges to strike a balance between punishing past offenses and obtaining future appeasement.It is a well-known fact that, during the changeover from Fascism to republic Italian, judges (in particular the second section of the Court of cassation) progressively adopted a less rigorous attitude towards collaborators. These results have been generally blamed on the fact that, on the whole, the judiciary had not been purged after the fall of Fascism, which in turn meant that sanctions against Fascism were not enforced.What about the decisions as far as regard young people charged with collaboration with the Germans? What were the reasons given by the judges to condemn or acquit them? And what the arguments used by the defendants and their lawyers against the charge of collaboration?Most of the trials against young people regarded the criminal responsibility of the juveniles.Between the 19th and the 20th centuries, the discipline of responsibility of minors based on balancing between juvenile delinquency and the immaturity of youth. The Penal Code of 1889 considered minors aged nine to fourteen responsible if they had acted with “discernment” (art. 54). As far as the Court of Cassation was concerned, the discernment of minors was not identified in their ability to recognize the moral gravity of the offense, as the liberal doctrine had suggested, but rather in their ability to recognize that such conduct was in violation of penal law. The elimination of the concept of discernment in the Fascist Penal Code did little to resolve the doubts of the courts. The Penal Code of 1930 required judges to evaluate the “mental capacity” of minors aged fourteen to eighteen (art. 98). Judges thus continued to demand that a minor’s maturity fit the crime, taking into account their physical and moral development, in addition to their relationships and their social, cultural and economic background.It is important to keep in mind that, as ruled by the special section of the Court of Cassation on the matter of collaboration with Germans, special court of assizes had exclusive jurisdiction also over minors, despite the fact that a juvenile court had been in operation since 1934.At first, special court of assize considered the juveniles responsible for the crimes of collaboration with Germans, but the punishment was mitigated according to art. 98 c.p. and the special section of the Court of cassation generally confirmed the judgements.The second section of the Court of cassation, instead, used to annul the sentences that considered the young people responsible for collaboration with Germans on the ground that judges had failed to provide the reasons of their judgements about the responsibility of minors and required that the evaluation of a minor’s mental capacity had to be related to the crime committed, especially if it was of a political nature.In particular, according to the arguments of the defence lawyers, the Court of Cassation ruled that judges had to consider that young people generally were not able to understand the wrongfulness of acts of collaboration, because of the Fascist propaganda.We have to keep in mind that in explaining the general amnesty of 1946, even the minister of justice Togliatti pointed out how difficult it had been for young generations to distinguish right from wrong during the Fascist period because of the discipline imposed by the regime.Doctrine agreed with jurisprudence in ruling that the responsibility of minors was to be evaluated less severely with regard to political crimes such as collaboration with the Germans, considering this approach to sentencing would help foster the peace process and educate the Italian youth that had been involved in the dramatic experience of the Civil War.
Keywords: Republic of Salò; Collaboration with the Germans; Minors; Transitional justice; Court of cassation